Dysbiosis and Schizophrenia: A Review of Current Evidence on the Gut–Brain Axis and Probiotic Interventions - Jakubiak, Anna; Karaban, Łukasz; Borawski, Michał; Ciuła, Aleksandra; Miśkiewicz, Joanna; Kuźnieców, Tadeusz; Paszkowska, Monika; Mularczyk, Klaudia; Znamirowska, Patrycja; Kupis, Magdalena (Quality in Sport, 2025)
Introdution: Schizophrenia is a complex mental disorder influenced by both genetic and environmental factors. Recent research has highlighted the potential role of the gut microbiota in mental health, including schizophrenia. Disruptions in gut microbiota composition, known as dysbiosis, may affect the central nervous system through immune modulation, neuroinflammation, neurotransmitter imbalance, and increased intestinal permeability. Notably, studies have shown associations between dysbiosis and the severity of psychotic symptoms as well as treatment response. Some evidence also suggests that probiotics may help alleviate certain psychiatric symptoms, including those seen in schizophrenia. Although further research is needed, probiotics are being investigated as a promising adjunctive therapy. Aim of the study: A literature review was conducted using PubMed and Google Scholar, covering studies from 2018 to 2025. Keywords included: "gut", "microbiome", "microbiota", "gut-brain axis", "dysbiosis", "schizophrenia", "antipsychotic drugs", "prebiotics", and "psychobiotics". Materials and Methods: A literature review was performed using PubMed, Google Scholar from 2018 to 2025, was conducted using keyword such as "gut", "microbiome", "microbiota", "gut-brain axis", "dysbiosis", "schizophrenia", "antipsychotic drugs", "prebiotics", and "psychobiotics". Summary The gut microbiota significantly influences mental health, and its disturbances may contribute to schizophrenia. Patients with schizophrenia often exhibit reduced microbial diversity and specific changes in microbiota composition, which may correlate with symptom severity. Antipsychotic medications also impact the microbiota. Prebiotics and probiotics appear to offer promising support to standard treatment, opening new avenues for therapeutic strategies.